CLINICAL FEATURES OF ACUTE RHEUMATIC FEVER IN PEDIATRIC PATIENTS: FINDINGS FROM A SINGLE-CENTER TERTIARY CARE HOSPITAL - Dr Kiran Fatima; Dr Sultan Mustafa; Dr Riffat Farrukh; Dr Ibrahim Shakoor; Dr Shaheen Masood; Dr Amber Naseer (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: To explore and record the clinical features of acute rheumatic fever in pediatric patients at a tertiary care hospital in Karachi, Pakistan.Methodology: Clinical features of acute rheumatic fever (ARF) in children aged 1 to 14 years was evaluated in this descriptive cross-sectional study, which took place at Abbasi Shaheed Hospital, Karachi Medical and Dental College, from January, 2023 to June 2023. Exclusions included co-morbidities like diabetes, kidney and liver diseases, inactive rheumatic heart disease, and HIV. Ethical approval and informed consent were obtained. Data collection encompassed medical history, physical exams, ECG, chest x-ray, and essential labs, with echocardiography performed on all participants. ARF diagnosis followed the Modified Jones Criteria, classifying carditis into no carditis, mild, moderate, and severe. Version 23.0 of the IBM-SPSS was utilized to analyze the data.Results: The study included 86 children with acute rheumatic fever (ARF), with a mean age of 8.4 ± 3.2 years; 65.1% were between 4-12 years old. The cohort comprised 62.8% females and 37.2% males, with 58.1% residing in rural areas. A significant number, 60.5%, had symptoms for over a month, and 19.8% had parents with no formal education. Arthritis was significantly more common in first episodes (70.8%) than recurrences (29.0%, p